Water isotope values and chemical parameters in time series samples (March 2020 - January 2021) from Müggelsee, Germany - Aichner, Bernhard; Dubbert, David; Harpenslager, Sarah-Faye; López Moreira Mazacotte, Gregorio Alejandro (In: Aichner, Bernhard; Dubbert, David; Kiel, Christine; Kohnert, Katrin; Ogashawara, Igor; Jechow, Andreas; Harpenslager, Sarah-Faye; Hölker, Franz; Singer, Gabriel; Grossart, Hans-Peter; Nejstgaard, Jens Christian; Wollrab, Sabine; Berger, Stella A; Goldhammer, Tobias; Schmid, Franziska; López Moreira Mazacotte, Gregorio Alejandro; Levertz, Constancia; Heidbüchel, Patrick; Müller, Uta; Hilt, Sabine (2021): Water isotope values from northeastern German lake systems 2020 et seq [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.935633, 2021)
Water isotopes (δ2H and δ18O) were analyzed in samples collected in lakes associated to major riverine systems in northeastern Germany throughout 2020. This sub-dataset is derived from water samples taken before the outflow of Müggelsee. Sampling was conducted biweekly from March 2020 to January 2021. Samples were taken with a pipette from 40-60 cm below water surface and directly transferred into a measurement vial. Isotope analysis was conducted at IGB Berlin, using a Picarro L2130-i cavity ring-down spectrometer. Water chemical and physical parameters are daily average values derived from the Müggelsee long-term data monitoring station (https://emon.igb-berlin.de/grosser_mueggelsee.html). The data give information about the seasonal isotope amplitude at Müggelsee over the studied time period.
Keywords: Dahme; Havel; Müritz; Spree; Ucker; δ18O; δ2H